The organised chaos of English adolescent rugby union: Influence of weekly match frequency on the variability of match and training loads - Phibbs, P. J.; Jones, B.; Roe, G.; Read, D.; Darrall-Jones, J.; Weakley, J.; Rock, A.; Till, K. (European Journal of Sport Science, 2018)
The aims of this study were to determine the variability of weekly match and training loads in adolescent rugby union players across a competitive season, and to investigate the effect of match frequency on load distribution across different activities. Internal match and training load data (i.e. session-rating of perceived exertion (sRPE)) were collected daily from 20 players from a regional academy across a 14-week season. Data were analysed using a mixed-effects linear model, and variability was reported as a coefficient of variation (CV). Differences between 0-, 1-, 2-, and 3-match weeks were assessed using Cohen`s d effect sizes and magnitude-based inferences. Mean weekly total match and training sRPE load was 1425 ± 545 arbitrary units (AU), with a between-player CV of 10 ± 6% and within-player CV of 37 ± 3%. Mean week-to-week change in total sRPE load was 497 ± 423 AU (35%), and 40% of weekly observations were outside the suggested acute:chronic workload ratio `safe zone`. Total weekly sRPE loads increased substantially with match frequency (1210 ± 571, 1511 ± 489, and 1692 ± 517 AU, for 0-, 1-, and 2-match weeks, respectively), except for 3-match weeks (1520 ± 442 AU). Weekly match and training loads were highly variable for adolescent rugby players during the competitive season, and match frequency has a substantial effect on the distribution of loads. Therefore, match and training loads should be coordinated, monitored, and managed on an individual basis to protect players from negative training consequences, and to promote long-term athlete development.